Transferencia y Transformación de Desechos Industriales - Castro-Portuguez, Grettel; Ferreto-Gutiérrez, Eugenia; Fournier-Zepeda, Ana María (Instituto Tecnológico de Costa Rica, 2010)
The project was to increase productivity and Transfer Center Material Transformation (CTTM) using the implementation of 5S and introduction of cleaner production processes, training your staff Administrative and environmental areas, opening new markets, and in turn introducing greater added value in some of its products. Actions that have made the CTTM more competitive and self-sustaining with safe and responsible management of industrial and institutional waste integral. In three years, productivity in terms of utilization of materials It increased by 99.14%, and further increase the level of participation supplier companies and institutions CTTM 385%, offering the market new forms of treatment, such as the electronic waste. Today CTTM is a formal activity that has become a center collection and processing of waste with social responsibility, which gives security and confidence to the institution or company receiving its services.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Química; Escuela de Administración de Empresas, 2010
Keywords: Reciclaje; Administración; Producción; Higiene; Sostenibilidad